2007
DOI: 10.2514/1.21565
|View full text |Cite
|
Sign up to set email alerts
|

Sub-Milli-Newton Class Miniature Microwave Ion Thruster

Abstract: A miniaturized microwave ion source with a 1.6-cm beam diameter grid system was designed and then evaluated experimentally. Based on the HAYABUSA 10 neutralizer, we fabricated a small 18-mm-diam discharge chamber, into which 4.2 GHz microwaves were launched through an L-shaped antenna that was located in a magnetic field created by permanent magnets and iron yokes. Ion beams were emitted from the small discharge chamber when operated with a grid system whose respective hole diameters of the screen grid and acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Since a few years ago, several researchers have studied a micro ion engine using microwave discharge 8,9) . The simple structure of a microwave discharge ion engine is suitable for the miniaturization.…”
Section: Micro Ion Engines and Previous Workmentioning
confidence: 99%
“…Since a few years ago, several researchers have studied a micro ion engine using microwave discharge 8,9) . The simple structure of a microwave discharge ion engine is suitable for the miniaturization.…”
Section: Micro Ion Engines and Previous Workmentioning
confidence: 99%
“…The action of the ions leaving the thruster causes a reaction that pushes the spacecraft in the opposite direction. [9][10][11][12][13][14] Wirz et al showed good performance of a 30 mm miniature xenon ion ͑MiXI͒ thruster, that is, the propellant utilization and the ion beam production cost were 0.8 and 500 W/A, respectively, for a mass flow rate of 0.02 mg/s. A pair of grids in the ion thruster accelerates the ions to very high speed, such as 30 000-80 000 m/s, and shoots them out of the thruster.…”
Section: Introductionmentioning
confidence: 99%
“…To date, several studies on miniature ion thrusters have been conducted for several different types of the plasma generators, namely direct current electron discharges, 11,12) radio frequency discharges, 13) and microwave discharges. [14][15][16][17] In spite of these benefits, however, miniature ion thrusters have not been employed on small spacecraft yet. This is mainly caused by two significant reasons.…”
Section: Introductionmentioning
confidence: 99%